Oryginalność Hieroklesowego porównania Apoloniusza z Tiany z Chrystusem - Tondera, Adam (Vox Patrum, 2016)
Sossianus Hierocles, governor of Bithynia and adviser of the emperor Diocletian, at the beginning of the “great persecution” of the Christians published his propagandistic writing under the title The Lover of Truth, in which he drew a comparison between Apollonius of Tyana and Christ. In the apologetic treatise of Eusebius of Caesarea Against Hierocles we find a statement, that this comparison was something new in the hitherto existing attacks of the pagan intellectuals on Christianity and demanded a polemic response from the Christian part. Modern studies regarding the works of Porphyry, famous enemy of the Christians and exponent of the Neo-Platonic philosophy, seem to indicate that even before Hierocles the personage of Apollonius was used in the anti-Christian polemics and was confronted with Christ. The present article try to explain, what the originality of Hierocles’ comparison, testified by Eusebius, consisted in.